Любовь и корона - Карнович Евгений Петрович (Ряд исторических романов, 1992)
Экземпляры: ф.22 (1993) / Инвентарный номер: 36820 / Цена: / Сис.шифр: 84(2Рос=Рус)1-4 / Авт.знак: К 24 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)1-442